Pseudomonas Diversity Within Urban Freshwaters - Batrich, Mary; Maskeri, Laura; Schubert, Ryan; Ho, Brian; Kohout, Melanie; Abdeljaber, Malik; Abuhasna, Ahmed; Kholoki, Mutah; Psihogios, Penelope; Razzaq, Tahir; Sawhney, Samrita; Siddiqui, Salah; et al. (Frontiers in Microbiology, 2019)
Freshwater lakes are home to bacterial communities with thousands of interdependent species. Numerous high-throughput 16S rRNA gene sequence surveys have provided insight into the microbial taxa found within these waters. Prior surveys of Lake Michigan waters have identified bacterial species common to freshwater lakes as well as species likely introduced from the urban environment. We cultured bacterial isolates from samples taken from the Chicago nearshore waters of Lake Michigan in an effort to look more closely at the genetic diversity of species found there within. The most abundant genus detected was Pseudomonas, whose presence in freshwaters is often attributed to storm water or runoff. Whole genome sequencing was conducted for 15 Lake Michigan Pseudomonas strains, representative of eight species and three isolates that could not be resolved with named species. These genomes were examined specifically for genes encoding functionality which may be advantageous in their urban environment. Antibiotic resistance, amidst other known virulence factors and defense mechanisms, were identified in the genome annotations and verified in the lab. We also tested the Lake Michigan Pseudomonas strains for siderophore production and resistance to the heavy metals mercury and copper. As the study presented here shows, a variety of pseudomonads have inhabited the urban coastal waters of Lake Michigan.